A ferrocene imidazolium-based macrocycle as an electrochemical chemosensor for halide anions - Caballero, A; White, N; Beer, P (Royal Society of Chemistry, 2014)
C4-H and C5-H protons of the imidazolium heterocycle have been exploited as a binding site for anion recognition in the design of two new redox-active imidazoliophane syn and anti isomers. The cooperative action of the two imidazolium motifs of the syn isomer is crucial for halide anion recognition. The integration of a ferrocene signalling unit at the C2 position of the imidazolium motif also facilitates the electrochemical sensing of anions by the syn isomer receptor. This journal is © the Partner Organisations 2014.